Heterogeneity in rent-seeking contests with multiple stages: Theory and experimental evidence - Tanja Hoertnagl; Rudolf Kerschbamer; Regine Oexl; Rudi Stracke; Uwe Sunde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
We investigate how heterogeneity in contestants' investment costs affects competition expenditures in a dynamic elimination contest with different seeding variants of contestants. Theory predicts that expenditures in dynamic contests are lower when competitors are heterogeneous than when they are homogeneous. Cost heterogeneity influences expenditures directly - by inducing weak and strong competitors to reduce their expenditures - and indirectly - through their influence on continuation values. We present evidence from lab experiments that is qualitatively in line with the theoretical prediction for contestants with low investment costs: they incorporate the heterogeneity and the differences in continuation values when competing in stage one and they decrease their expenditures when competing against a weak agent in stage two. For high-cost contestants, the theoretical predictions are not confirmed: expenditures in heterogeneous interactions are not lower and sometimes even higher. As a consequence, we find that total expenditures in heterogeneous dynamic contests are not necessarily lower than in homogeneous ones.
Keywords: C72; D72; 330; Multi-Stage Contest; Heterogeneity; Experiment